Adherent cells from rheumatoid synovia: identity of HLA-DR positive stellate cells. Issue 2 (February 1987) - Heino, J; Viander, M; Peltonen, J; Kouri, T
Abstract : Rheumatoid synovia were enzymatically digested and the in vitro morphology of different types of plastic adherent cells was observed. Four main types of cells were found after 24 hours in culture: stellate cells which had nuclei resembling those of classical cultured fibroblasts, but which stained positively with I2 antibody (anti-HLA-DR antibody); fibroblastic cells; cells which resembled morphologically in vitro macrophages and which were I2 and OKM-1 positive; round monocytes. The stellate cells did not stain with anti-S-100 or OKT-6 antibodies, which are used to detect classical antigen presenting dendritic cells. Furthermore, in the presence of indomethacin the stellate shaped cells were replaced by new I2 positive cells with a typical fibroblast shape. These results support the view that the stellate cells in synovial cell cultures represent HLA-DR positive fibroblasts, probably B cells of synovial lining.